Partisipasi Kristiani dalam Pekerjaan Tuhan: Perspektif Antropologi St. Gregorius dari Nyssa” - Purnama Gulo , Wiki; Batawi , Andrians (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2025)
Participation in the work of the Christian God often experiences getting stuck, such as feeling bored, tired and even refusing to participate. This problem is caused by a lack of Christian understanding regarding human origins from creation to redemption. So to overcome this problem, the author uses Qualitative methods by analyzing journals, books, and interacting with Biblical texts in order to obtain results that can obercome the problems above. But the main focus to get answers to the problems above, the author uses the Anthropology of St. Gregorius who provides an understanding of who humans really are. The goal is for Christians to realize the importance of participating in God’s work. By learning to understand who humans really are through Gregorius understanding.